Ðœanaging Landed Capital: Methodology and Procedure of Absolute Rent Calculation - Sharyi, Hryhorii; Dubishchev, Viktor; Kobets, Serhii; Kariuk, Alla (International Journal of Engineering and Technology, 2018)
The methodological principles of land relations and land assessment institutionalization have been substantiated and presented in this article. The authors have also gave grounds for the ways of solving the problems of objective definition of the absolute rent assessment mechanism taking into account the peculiarities of modern land use.There have been considered various options of assessing the possible receipt of the absolute rental value, which took into account cereal crops and where there were selected the most important crop plants in the crop structure of Poltava region.The article defines two basic methods of calculating the normative monetary evaluation of land, which are legally constituted and are in force today. But the problem is that they duplicate each other without specifying the mechanism for establishing absolute rental income on agricultural lands.In the article there have been considered different variants of assessing the possible receipt of the absolute rental value and organization of ecologically and economically efficient changes in sowing. The authors have also introduced the formation model of the social value of establishing prices for agricultural products.As a result, the received absolute rent reflects the formation mechanism of the surplus value above the rate of profit.Â Â